正中神経の走行上に存在する郄門への経穴刺激理学療法抑制手技が母指外転筋に対応した脊髄運動神経機能に与える影響 - 安井, 柚夏; 東藤, 真理奈; 鈴木, 俊明; 松下, 可南子; 島地, 陽登; 伊藤, 夢基; 谷, 万喜子; 前田, 翔梧; 福本, 悠樹 (関西理学療法, 2020)
This study aimed to clarify the change of the spinal motor neural function effected by ASPT (acupoint stimulation physical therapy) of Ximen. ASPT is physical therapy using acupuncture stimulation. This study enrolled twenty healthy subjects and examined the change of the spinal motor neural function in them. First, the F-wave of resting was measured. Next, we performed ASPT of Ximen and measured the F-wave during ASPT, and at 0, 5, 10, and 15 minutes after ASPT. F-wave persistence was significantly decreased at 0, 5, 10, and 15 minutes after ASPT compared with that during ASPT. The F/M amplitude ratio did not significantly decrease at any time. Therefore, no significant difference was observed between rest and any of the other times. Based on these results, we consider that pain stimulation of Ximen does not affect spinal motor nerve function.